Projet d’urbanisme : ordre social, ordre politique. Bogotá 1900-1951 - Diego Arango Lopez (Centre de Recherches sur les Mondes Américains, 2013)
This article seeks to understand the processes of production, institutionalization and reception of urban projects in Bogotá in Colombia during the first half of the twentieth century. The paper reveals an analysis of the construction of a bureaucracy in the local government, followed by an exploration of the first urban projects and their reception. It concludes that during this period the institutional, social and political structures of the city created a complex urban planning system.